COVID-19 Efforts at the Institute of Image Guided Surgery (IHU-Strasbourg): 2020. (April 2021) - Swanstrom, Lee; Perretta, Silvana; Pizzicannella, Margherita; Rodriguez-Luna, Maria Rita; Verde, Juan; Garcia, Alain; Gallix, Benoit
We submit a summary of some of the activities of the IHU-Strasbourg during the initial period of the COVID-19 pandemic. These were presented as part of the coronnavation effort coordinated by Dr Adrian Park. Three initiatives are presented as follows: Protect-Est App, healthcare worker stress, and converted diving mask for ventilation. Two of the 3 projects are still ongoing, and one (Predoict-Est) has been adopted nationally.